2023
DOI: 10.1093/sleep/zsad013
|View full text |Cite
|
Sign up to set email alerts
|

The role of sleep and heart rate variability in metabolic syndrome: evidence from the Midlife in the United States study

Abstract: Study Objectives Poor sleep and autonomic dysregulation can both disrupt metabolic processes. This study examined the individual and combined effects of poor sleep and reduced heart rate variability (HRV) on metabolic syndrome among 966 participants in the Midlife in The United States II study (MIDUS II). Methods Self-reported sleep was assessed using the Pittsburgh Sleep Quality Index (PSQI). HRV was acquired from 11-minute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Sleep disturbances elicit stress and chronically can disrupt the ability of the ANS to modulate sympathetic nervous system activity ( 69 , 70 ). A recent study reported an increased odds of metabolic syndrome, a cancer risk factor ( 71 ), among those with both poor sleep and low heart rate variability (HRV, an indicator of dysfunctional autonomic activity), relative to those with normal sleep and HRV ( 72 ). This and other evidence indicates that chronic stress leads to a pro-inflammatory state of sympathetic overactivation and ANS dysregulation ( 73 , 74 ) that can promote tumorigenesis ( 73 77 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sleep disturbances elicit stress and chronically can disrupt the ability of the ANS to modulate sympathetic nervous system activity ( 69 , 70 ). A recent study reported an increased odds of metabolic syndrome, a cancer risk factor ( 71 ), among those with both poor sleep and low heart rate variability (HRV, an indicator of dysfunctional autonomic activity), relative to those with normal sleep and HRV ( 72 ). This and other evidence indicates that chronic stress leads to a pro-inflammatory state of sympathetic overactivation and ANS dysregulation ( 73 , 74 ) that can promote tumorigenesis ( 73 77 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given the importance of HRV methodology and the fact that most studies were large-scale epidemiological ones, if specific details of HRV methodology were not directly mentioned in the original article they were retrieved, when possible, from study protocol documentation or related publications from the same wave of the study. This is indicated by a superscript letter in the relevant Tables ( Table 1 and Supplementary Table S1 , superscript letters c and a respectively) and the additional references used for each study are provided in Supplementary Table S2 [ 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ].…”
Section: Methodsmentioning
confidence: 99%
“…The global epidemic of MetS has become a significant public health problem of worldwide concern [ 2 ]. MetS is typically characterized by a complex combination of risk factors, including hypertension, hyperglycemia (impaired glucose tolerance), dyslipidemia and abdominal obesity [ 3 ], which might significantly increase the risk for cardiovascular diseases and diabetes. In addition, patients with MetS may have disturbances in the gut microbiome, including decreased beneficial microbes and increased harmful ones [ 4 ].…”
Section: Introductionmentioning
confidence: 99%